HUBUNGAN KEHARMONISAN KELUARGA DENGAN KEMAMPUAN MENGELOLA EMOSI MAHASISWA - Agung pebrianto; Ninil elfira; Utami Niki Kusaini (IKIP Siliwangi, 2026)
The ability to manage emotions is an important aspect in the psychological development of students in the early adulthood phase. The family environment, especially the level of family harmony, is often seen as a factor that influences an individual's emotional development. However, empirical findings show that the relationship between family harmony and the ability to manage emotions is not always positive. This study aims to analyze the relationship between family harmony and the ability to manage emotions in students of the Guidance and Counseling Study Program, Jambi University, Class of 2023. This study used a quantitative approach with a correlational design. The study population consisted of 101 students and all were sampled through a total sampling technique, with the limitation of the sample of students coming from complete nuclear families. The research instruments were a family harmony scale and an emotion management scale that had met validity and reliability tests. Data analysis was carried out using Pearson Product Moment correlation with the help of IBM SPSS Statistics 26. The results showed a negative and significant relationship between family harmony and the ability to manage emotions (r = -0.258; p = 0.009). These findings indicate that high family harmony is not always followed by high emotion management abilities in students. The results of this study are expected to provide theoretical contributions to the study of family psychology and practical implications for guidance and counseling services in higher education.